Measuring adhesion on rough surfaces using atomic force microscopy with a liquid probe - Juan V. Escobar; Cristina Garza; Rolando Castillo (Beilstein Journal of Nanotechnology, 2017)
We present a procedure to perform and interpret pull-off force measurements during the jump-off-contact process between a liquid drop and rough surfaces using a conventional atomic force microscope. In this method, a micrometric liquid mercury drop is attached to an AFM tipless cantilever to measure the force required to pull this drop off a rough surface. We test the method with two surfaces: a square array of nanometer-sized peaks commonly used for the determination of AFM tip sharpness and a multi-scaled rough diamond surface containing sub-micrometer protrusions. Measurements are carried out in a nitrogen atmosphere to avoid water capillary interactions. We obtain information about the average force of adhesion between a single peak or protrusion and the liquid drop. This procedure could provide useful microscopic information to improve our understanding of wetting phenomena on rough surfaces.